Cost–benefit Analysis of Introducing Organ Transplant in the Ayushman Bharat Pradhan Mantri Jan Arogya Yojana - Shyamli Varshney; Pooja Kansra; Anurag Garg; K. Avinash; Shalender Singh; A K Amiya (Indian Journal of Transplantation, 2025)
Introduction: Solid organ transplantation causes an escalating financial burden of medical care, which was not included in the AyushmanBharat – Pradhan Mantri Jan Arogya Yojna (AB-PMJAY), leading to a lesser number of patients opting for organ transplant, especially from lower socioeconomic strata (below poverty line) population. Methods: A qualitative study based on focused group discussion was conducted across 14 transplant hospitals in Haryana, focusing on individuals with exposure to organ transplantation. In-depth interviews were conducted to assess the costs and benefits of organ transplantation, along with the associated challenges and intricacies. The study provided a deeper and more nuanced understanding of the implementation dynamics and cost factors that may influence the success of the transplant process. Results: Postorgan transplant, approximately 75% of recipients rated their quality of life as equal to or above average. Discussion: It is imperative for the government to launch initiatives that provide better medical care, enhance longevity, and enable recipients to fulfill their responsibilities effectively. The organ transplant package is a recent addition to the ambit of the AB scheme. If executed properly, this initiative has the potential to assist individuals in handling their healthcare costs and reduce their financial strain. Conclusion: The inclusion of Organ Transplantation in AyushmanBharat – Pradhan Mantri Jan Arogya Yojna (AB-PMJAY) is a landmark decision in India’s quest for health equity ensuring that lifesaving treatments are not just a privilege for the affluent but a right for all citizens.